GA Document 158 : International 2021 - Futagawa, Yoshio; Saito, Hitomi; Nakamura, Akiyo; Sekimoto, Reiko (Tokyo : A.D.A. EDITA Tokyo Co., Ltd., 2021)
Steven Holl ; Sanaa ; Kazuyo Sejima ; Junya Ishigami ; Kengo Kuma ; Kajima design
boek